The Effect of Dow Jones Industrial Average, FTSE 100 and Hangseng on Joint Stock Price Index on the Indonesia Stock Exchange in the Period of 2020 - Marselia Purnama; Octavianti Purnama; VIVIN HANITHA (eCo-Buss, 2021)
At the time of the Covid 19 pandemic in Indonesia, the economy became increasingly difficult, so many factories had difficulty surviving, and laid off their employees. As an effort to stay afloat, many laid-off employees have started investing in the capital market in order to continue to earn income and to fill time while looking for new jobs. This is evidenced by the increase in retail investors in 2020 to 3,615,000 investors. This number increased by 45.51% from the number of investors in the previous year, namely 2019. With so many new investors, the easiest thing to do to analyze stock price movements is to look at stock movement indexes in other countries, such as the Dow Jones Industrial Average, FTSE 100 and Hangseng. This research was conducted on the Indonesia Stock Exchange, by looking at the movement of the Composite Stock Price Index. The researcher uses a purposive sampling method to take samples with the criteria of the time period used is during 2020. The object of this research is the effect of the Dow Jones Industrial Average, FTSE 100, Hangseng on the Composite Stock Price Index from January 2020 to December 2020, and obtained data number 225. Hypothesis testing using Classical Assumption Test, Multiple Linear Regression Analysis, Simultaneous Test (f test), Partial Test (t test), and Coefficient of Determination Test. The results of the Key Test show that the Dow Jones Industrial Average, FTSE 100, and Hangseng have a significant effect on the JCI partially and simultaneously during the study period, with the adjusted number R2 or 92.57%, while the remaining 7.43%. in this research.